Oud neg.nr. 75944-75974. 'Horecabond, kantoor, bondsbestuur, bestuurders-distriktbestuurders' - Haas, Joh. de,
Oud neg.nr. 75944-75974. 'Horecabond, kantoor, bondsbestuur, bestuurders-distriktbestuurders'.